Microwave diathermy - L. Hayward; A. Statham (AOSIS, 1981)
An extensive literature survey is summarised. Experimentation consisted of irradiation of paraffin wax and human subjects with microwave of frequency 2 450 MHz Results, conclusions and recommendations are briefly stated. A full reference list is given.